Effect of Laryngeal Mask Air Way Insertion versus Endotracheal Intubation over Hemodynamic Responses in Pediatrics Patient Who Underwent Ophthalmic Surgery at Menelik II Hospital, Addis Ababa: A Prospective Observational Study Design - Mohammed Suleiman Obsa; Azeb Lencha Sholla; Betelhem Girma Baraki; Getahun Dendir Welde; Temesgen Bati Gelgelu; Melese Meleku Kuruche (Anesthesiology Research and Practice)
Background. The airway of an anesthetized child is usually maintained with an endotracheal tube or laryngeal mask airway. However, both are related with some level of pressor response which may be risky in several groups of patient. Methods. An institutional-based prospective observational study design was employed. A systematic random sampling technique was used to select study participants. Data were entered into Epi info version 7 and transported to SPSS version 20 for analysis. Normality of the data was checked using Shapiro–Wilk tests. An independent t test was used to determine the mean differences between the two groups while the paired sample t test was used to determine the mean differences within the groups. A p value of less than 0.05 was used as a cut-off point for the presence of association. Results. The changes in systolic and diastolic blood pressure were returned to baseline values at five and three minutes in both groups, respectively. However, the changes in the heart rate and mean arterial pressure returned to baseline values in five minutes in the ETT group and three minutes in the LMA group. At baseline, the difference in systolic blood pressure between the two groups was not statistically significant (p=0.328). Conclusions. A significant hemodynamic pressor response was observed after the insertion of both LMA and ETT groups. However, the LMA group has less hemodynamic change as compared to the ETT group. Therefore, the practice of LMA insertion was strongly recommended.